An Interventional Study on the Effectiveness of Proprioceptive Neuromuscular Facilitation (PNF) in the Rehabilitation of Patients with Bell’s Palsy - Yadav, Savitri; Lohar, Deepak; Khan, Jafar; Warsi, Rahat khan; Menria, Shubham; Pal, Renuka; Balala, Deepika; Rai, Richa Hirendra; Rawat, Praveen; Vashi, Achalkumar (Journal of Neonatal Surgery, 2025)
Background:Bell’s palsy is the most common cause of unilateral lower motor neuron facial paralysis, often resulting in sudden facial weakness, asymmetry, and loss of voluntary facial expressions. It significantly impacts patients' physical, emotional, and social well-being. While many cases resolve spontaneously, delayed or inadequate treatment can result in long-term dysfunction. Among physiotherapeutic interventions, Facial Proprioceptive Neuromuscular Facilitation (PNF) has emerged as a promising technique aimed at enhancing neuromuscular recovery and facial symmetry. Objective:To evaluate the effectiveness of Facial Proprioceptive Neuromuscular Facilitation (PNF) as a standalone intervention in improving facial muscle function, coordination, and symmetry in patients with Bell’s palsy. Methodology:This interventional study was conducted at Pacific Medical University & Hospital, Udaipur, with 30 patients diagnosed with unilateral Bell’s palsy. Participants underwent a structured 8-week PNF-based rehabilitation program, consisting of daily supervised sessions for 6 days a week, each lasting approximately 20 minutes. Techniques included diagonal movement patterns, manual resistance, visual and verbal cues, and proprioceptive stimulation targeting key facial muscles. Progress was assessed using the House-Brackmann Facial Nerve Grading System pre- and post-intervention. Statistical analysis was performed using paired t-tests. Results:The study demonstrated a statistically significant improvement in facial nerve function following PNF intervention. The mean House-Brackmann score improved from 4.83 ± 0.75 to 1.80 ± 0.82, with a mean difference of 3.03, t-value of 15.42, and p-value < 0.005, indicating a substantial recovery in muscle symmetry and function. Conclusion:Facial PNF is an effective, non-invasive, and evidence-based physiotherapeutic intervention for Bell’s palsy rehabilitation. It significantly enhances facial muscle strength, coordination, and voluntary control, supporting its role as a primary rehabilitation strategy in early management of Bell’s palsy